Analysis of a double-beam e,X-mode at an idustrial accelerator “EPOS” - Uvarov, V.L.; Zakharchenko, A.A.; Zarochintsev, L.V.; Tenishev, A.Eh.; Titov, D.V.; Tytov, V.Yu. (Вопросы атомной науки и техники, 2020)
The main assignment of industrial plant with an accelerator “EPOS” providing the electron energy up to 30 MeV is radiation dyeing of gemstones. At treatment of them, the part of the electron energy is transformed into bremsstrahlung (X-) radiation. The energy characteristics of the electron beam were measured by a dosimetry wedge technique. On the basis of obtained results, the parameters of the mixed e,X-flux (the energy conversion coefficient and the factor of secondary radiation) along the path of radiation formation were alculated using a transport code GEANT4. The conditions for production of X-ray radiation in the state of electronic equilibrium have been determined. The spectrum of the X-ray photons as well as the dose rate and its distribution behind a target device for gemstone irradiation were calculated. A measured dose profile is satisfactory agreed with the data of the simulation. Implementation of a double-beam mode enables to conduct the extra radiation programs in the field of the bremsstrahlung radiation (modification of semiconductors and polymers, radiation tests, photonuclear activation of samples, etc.).